A comparison of the compositions of acidic and basic fractions in <300 °C fractions from six Chinese shale oils. (1st January 2018) - Cui, Da; Wang, Qing; Wang, Ping; Chi, Mingshu; Pan, Shuo; Liu, Bin
Abstract: Shale oil samples were obtained from the pyrolysis of six Chinese representative oil shales obtained from different locations and were divided into <300 °C and >300 °C fractions according to their boiling points. Chinese shale oils were similar in their high atomic H/C ratio. Huadian shale oil possessed the lowest density and viscosity. <300 °C fractions of shale oils were subjected to acidic/basic liquid separation to prepare the acidic, basic and neutral fractions. In this paper, the acidic and basic fractions were characterized by gas chromatography-mass spectrometry. The results show that the <300 °C fraction of shale oil had large amounts of acidic and basic components, consisting of oxygen containing compounds and nitrogen containing compounds. The intrinsic characteristics and metamorphic degree of kerogen determine the relative content of acidic and basic compounds in shale oil. The relative content of phenols was the highest in acidic compounds, and ranged from 78.24% to 86.84%. The relative content of lower phenols was significantly higher than that of the higher phenols. C4 -phenols seldom appeared in the acidic fraction of <300 °C fraction. For the basic fractions, anilines, pyridines, quinolines and other nitrogen containing compounds with aromatic ring were identified. The relative content of pyridines in Longkou and Maoming basic fractions was obviously more than those in other samples, and was 22.2% and 22.53%, respectively. C2 -aniline, C2 -pyridine and C1 -quinoline compounds were dominant in the basic fraction of <300 °C fraction.